Ohne Fleiß kein Preis – die deutsche Volkswirtschaft muss sich ihre Innovationsfähigkeit immer wieder neu erarbeiten - Christoph M. Schmidt (Wirtschaftsdienst, 2024)
– The medium-term prospects for the German economy give little cause for optimism. In addition, demographic change will intensify in the current decade. A brightening of growth prospects can therefore only materialise with stronger investment and greater innovation momentum. However, it will hardly be enough to directly promote this through economic policy interventions if the available pool of adaptable and skilled labour cannot be strengthened. This will require a wide range of economic policy endeavours.
Keywords: O40; E23; J21; 330; Wirtschaftslage; Wirtschaftspolitik; Deutschland; Wirtschaftslage; Wirtschaftspolitik; Deutschland